Bridging the Gap : Improving Capabilities and Expanding Opportunities for Women in the Middle East and North Africa Region - World Bank (Washington, DC, 2017)
This brief summarizes some of the significant constraints women in Middle East and North Africa (MENA) face: limited labor market mobility, a mismatch between skills acquired in school and what is in demand in the labor market, and legal or institutional factors related to cultural norms, all of which inhibit the transition from school to work. The brief identifies various policy options and outlines the World Bank's strategy for supporting governments in achieving gender parity in the region. Rigorous analytical work, experimental policy pilots and lending operations with a strong gender focus all form part of the Bank's strategy towards reducing gender gaps in economic opportunities.